2005
DOI: 10.1016/j.jacc.2005.04.052
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Clinical Significance of Left Atrial Remodeling in Competitive Athletes

Abstract: In a large population of highly trained athletes, enlarged LA dimension > or = 40 mm was relatively common (20%), with the upper limits of 45 mm in women and 50 mm in men distinguishing physiologic cardiac remodeling ("athlete's heart") from pathologic cardiac conditions. Atrial fibrillation and other supraventricular tachyarrhythmias proved to be uncommon (prevalence < 1%) and similar to that in the general population, despite the frequency of LA enlargement. Left atrial remodeling in competitive athletes may… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
161
2
6

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 390 publications
(191 citation statements)
references
References 32 publications
17
161
2
6
Order By: Relevance
“…In line with previous studies, athletes have larger left atrial volumes compared to gender matched controls (6)(7)(8). Furthermore, this study shows that right atrial volumes increase with increasing fitness.…”
supporting
confidence: 92%
See 2 more Smart Citations
“…In line with previous studies, athletes have larger left atrial volumes compared to gender matched controls (6)(7)(8). Furthermore, this study shows that right atrial volumes increase with increasing fitness.…”
supporting
confidence: 92%
“…Few studies have investigated the effects on atrial volumes. Using echocardiography and cardiac magnetic resonance imaging (CMR), recent studies have shown increased atrial dimensions and volumes in endurance athletes (6)(7)(8). However, studies of atrial adaptation to training in women are scarce and data on the effects on right atrial volumes in both men and women is lacking.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…26 Highly trained individuals develop cardiac adaptations including enlarged LV and RV volumes, increased LV wall thickness and cardiac mass, and increased left atrial size. [21][22][23] In the general population, these structural changes are associated with poor cardiac prognosis. 27 However, these structural alterations, together with a preserved LV ejection fraction (EF), have been considered typical findings of the "athlete's heart."…”
Section: Athlete's Heartmentioning
confidence: 99%
“…350,351 Indeed, AF is the primary arrhythmia observed in middle-aged athletes. 352 AF in athletes tends to be paroxysmal, vagally mediated, and highly symptomatic.…”
Section: Section 3: Modifiable Risk Factors For Af and Impact On Ablamentioning
confidence: 99%